Impact of Constructive Marketing Strategies on Return (Revenue & Profitability): A Case Study of Mcdonald’s - Azim, Parvez; Azim, Samreen (Journal of Asian Business Strategy, 2012)
This paper contains the analytical view of the marketing strategic shift of McDonald’s and its effectiveness with respect to the growth of the company. Marketing strategies of the company are discussed in the three dimensions, which are marketing philosophy, company’s status with respect to the time of entrance in the market, and nature of the market served. Company continued to retain the strategies of market pull and national high share in the first and third dimensions respectively since its origination. But company shifts its marketing strategy from frontal attack to leap frog in the second dimension of marketing strategy analysis. In the year 2004, McDonald’s aligned its marketing strategies keeping in view the changing trends towards healthy and diet food from rich (fatty food) and nutritious food.Due to this strategic shift, the company not only protected the growth of its market share but also achieved record increase in revenue of 10%. A record increase of 55% in the net income along with the record increase of 19% in cash from operations which proved not only the efficiency but also the effectiveness of changed marketing strategies of McDonald’s. This pace of the growth of the company continued in later years also with a little fluctuation due to international economic crisis. The ill effects of the fast food have also been mentioned in this paper.